1996
DOI: 10.1002/eji.1830261215
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic regulation of CD8+ T cells after antigen challenge in the absence of Fas (CD95)

Abstract: The role of Fas in the homeostatic regulation of CD8+ T cells after antigen challenge was analyzed in the murine model of lymphocytic choriomeningitis virus (LCMV) infection. Mice homozygous for the lpr mutation and carrying T cell receptor (TCR) alphabeta transgenes specific for the LCMV glycoprotein peptide aa 33-41 in the context of H-2Db were used. Five main results emerged: first, development of lymphadenopathy and of CD4- CD8- double-negative B220+ T cells in lpr mice was not inhibited by the alphabeta T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 52 publications
4
48
1
Order By: Relevance
“…We found that approximately 30% of specific CTL had reverted to a CD62L high phenotype (indicative of resting T cells) in control mice, in keeping with previously published data [35]. In contrast, in MHC class II -/-and CD40 -/-mice, the frequency of memory CTL (tetramer + CD8 + ) expressing CD62L high was only 3% and 6%, respectively (Fig.…”
Section: Enhanced Activation Of Memory Ctl In the Absence Of Functionsupporting
confidence: 91%
“…We found that approximately 30% of specific CTL had reverted to a CD62L high phenotype (indicative of resting T cells) in control mice, in keeping with previously published data [35]. In contrast, in MHC class II -/-and CD40 -/-mice, the frequency of memory CTL (tetramer + CD8 + ) expressing CD62L high was only 3% and 6%, respectively (Fig.…”
Section: Enhanced Activation Of Memory Ctl In the Absence Of Functionsupporting
confidence: 91%
“…In fact, it was later demonstrated that activated T cells from TNFR2 -/-mice were resistant to Fas-induced apoptosis [25]. It has been shown in mouse models that only CD8 + T cells from Fas knockout mice are resistant to AICD [23], while in vivo studies have given no role [21,22,26], only a limited role [24] or a main role [27][28][29] to Fas-induced apoptosis in the down-modulation of immune responses mediated by CD8 + T cells. Few studies have analyzed this subject in human CD8 + T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies performed in mice models suggested that while CD4 + T cells were deleted mainly via Fas/FasL, CD8 + T cells were deleted via TNF/ TNFR2 [19,20]. However, other studies did not support such a role for TNF in CD8 + T cell down-modulation [21][22][23][24]. In fact, it was later demonstrated that activated T cells from TNFR2 -/-mice were resistant to Fas-induced apoptosis [25].…”
mentioning
confidence: 99%
“…Although in vivo data give clues about the tropism of viruses, MHC dependence (Moskophidis et al, 1994b), and the role of different molecules (Alexander-Miller et al, 1996;Zimmermann et al, 1996), our knowledge of the underlying mechanisms of clonal exhaustion is limited. Zinkernagel et al explain the cause of early clonal exhaustion in terms of total and sudden differentiation (Zinkernagel et al, 1993Zinkernagel, 1996); and argue that in overwhelming infections almost all CTL precursors differentiate into the short-living, nonproliferating effector phenotype and thus they disappear during the second week of immunization [see also Grossman (1986), Grossman et al (1986)].…”
Section: Introductionmentioning
confidence: 99%
“…This choice is supported by the following experimental evidence. First, CD8 + T lymphocytes are susceptible to direct apoptosis induction via binding TNF-α (Zheng et al, 1995;Alexander-Miller et al, 1996) or Fas/FasL interaction (Zimmermann et al, 1996). The innate immunity, especially activated macrophages and NK cells, produce large quantities of TNF-α (Eigler et al, 1997;Horwitz et al, 1997).…”
Section: Introductionmentioning
confidence: 99%